Community Empowerment Strategy Based on Local Potential through the Seed Garden Tourism Village Program in Kediri Regency - Isnaini, Rizqi Nur; Yuliati, Nanik; Ariefianto, Lutfi (Universitas Pendidikan Indonesia (UPI), 2023)
The development of tourism destinations in Indonesia is a development that is intensively carried out by the central government and local governments. A characteristic of a tourist village has the concept of a form of integration between attractions, accommodation, and fulfillment of facilities in a community structure that is integrated with traditions and procedures that already apply. Determination of the place in the study that is using a purposive area, because the selection of the place is based on certain considerations. The technique of determining the informants in this study used snowball sampling. Data collection techniques using the method of observation, interviews and documentation. Techniques for checking the validity of the data used extended participation, persistence of observation, and triangulation. The triangulation used is technique triangulation and source triangulation. Data analysis using Miles and Huberman includes: data collection, data reduction, data presentation and data verification. The results of this study indicate that there is a community empowerment strategy carried out by residents around Jambu Village to improve the standard of living of the local community.